After the public turn composition, counterpublics, and the citizen bricoleur - Farmer, Frank, 1951- (Utah State University Press, 2013)
"In After the Public Turn, author Frank Farmer argues that counterpublics and the people who make counterpublics--"citizen bricoleurs"--deserve a more prominent role in our scholarship and in our classrooms. Encouraging students to understand and consider resistant or oppositional discourse is a viable route toward mature participation as citizens in a democracy. Farmer examines two very different kinds of publics, cultural and disciplinary, and discusses two counterpublics within those broad categories: zine discourses and certain academic discourses. By juxtaposing these two significantly different kinds of publics, Farmer suggests that each discursive world can be seen, in its own distinct way, as a counterpublic, an oppositional social formation that has a stake in widening or altering public life as we know it. Drawing on major figures in rhetoric and cultural theory, Farmer builds his argument about composition teaching and its relation to the public sphere, leading to a more sophisticated understanding of public life and a deeper sense of what democratic citizenship means for our time"--